UPAYA PENINGKATAN KONEKSI MATEMATIS SISWA MELALUI PEMBELAJARAN ROLE PLAYING PADA MATERI PEMBAGIAN DI KELAS 2 MI ISLAMIYAH ROWOSARI - Ayu lestari, Eva; Rachamat Imam Muslim; Dian Kusumawati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research explores students’ mathematical connection skills at the second-grade level, which represent a crucial component of meaningful mathematics learning. The study was designed to strengthen the ability of Grade 2 students at MI Islamiyah Rowosari to establish mathematical connections in division topics through the application of a role-playing instructional model, while also examining the stages of its implementation in classroom practice. The investigation was structured within a Classroom Action Research (CAR) methodology and executed across two iterative stages, engaging 21 students as research subjects, comprising 11 female and 10 male participants. Each cycle followed a systematic “sequence of planning, instructional action, observation, and reflection”. Data were gathered through multiple techniques, including classroom observations, learning achievement tests, questionnaires, interviews, and documentation. Quantitative analysis was applied to evaluate improvements in learning outcomes and mastery levels, whereas qualitative analysis was used to examine the dynamics of the learning process. Implementation of the role-playing learning model led to a pronounced improvement in students’ ability to establish mathematical connections, demonstrated by the substantial growth in average achievement from 47.2% in the first cycle to 88.0% in the second cycle. The findings indicate that students became increasingly capable of linking division concepts with real-world contexts. Consequently, the role-playing learning model can be regarded as an effective alternative approach for enhancing mathematical connection skills in division instruction for Grade 2 students at MI Islamiyah Rowosari. Keywords: connecting mathematicals, role playing, mathematical, elementary school